Authentic Leadership Influences Bangkok Metropolitan Administration Schools’ Learning Organization through Teachers’ Psychological Capital and Organizational Commitment: A Structural Equation Model - Akkakanjanasupar P. (2023)
The research aimed to develop the structural equation model of learning organization affected by authentic leadership through mediators, psychological capital, and organizational commitment as perceived from the empirical data from Bangkok Metropolitan school teachers. The hypothesized model was examined using structural equation modelling among a sample consisting of 1,080 teachers. The findings revealed that causal relationships of learning organizations affected by authentic leadership through mediators fit the data well, as indicated by fit indices; authentic leadership engaged the highest significant effect on psychological capital, tailed by learning organization and organizational commitment. Authentic leadership significantly received the indirect effects on learning organization with a total effect through psychological capital and organizational commitment. There were direct effects of psychological capital on organizational commitment and learning organization. The findings indicated that the highest impacts of psychological capital were on learning organization, while learning organization was correspondingly influenced by authentic leadership and organizational commitment. The squared multiple correlations verified 79.10% of psychological capital, 65.90% of organizational commitment, and 68.40% of learning organization in the variances of authentic leadership, 68.40% of psychological capital and 65.90% of organizational commitment, had indicated the variances in the model.